PELATIHAN KADER TENTANG PSIKOEDUKASI KELUARGA SEBAGAI SUPPORT SYSTEM IBU HAMIL DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR : PELATIHAN KADER TENTANG PSIKOEDUKASI KELUARGA SEBAGAI SUPPORT SYSTEM IBU HAMIL DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR (STIKes Mitra Keluarga, 2022)
Pregnant women are prone to have physical and mental health problems. Mental health problems that occur during pregnancy can persist for some time after delivery. One thing that is needed by pregnant women during their pregnancy is the presence of a support system or people who provide support. Anyone can be a support system for a pregnant woman, for example husband, parents, siblings, and friends. The support system aims to support pregnant women so they don't get stressed during their pregnancy. Cadres are voluntary workers in the health sector who are directly elected by and from the community whose task is to assist in the development of public health. This community service activity aims to increase Cadre knowledge about family psychoeducation as a support system for pregnant women. In this community service activity, pre-test and post-test were carriedout through a questionnaire to see the level of knowledge of Cadres. The results of the pre-test and post-test showed that there was an increase in knowledge with a pre-test score of 68.3% to 96.6% in the post-test. This shows that this training and mentoring activity is effective in increasing Cadre knowledge.